Magnetic Properties of Fe-Si Electrical Steel after Laser Scribing - K. Ścibisz; J. Krawczyk (Archives of Metallurgy and Materials)
Improvement of magnetic properties of electrical steel can be achieved by reduction the size of magnetic domains. The application of local stresses through laser scribing leads to reduced core losses. In order to determine the effect of laser refinement conditions of magnetic domains on the properties of the soft magnetic material, four samples with a thickness 0.23 mm were refined. The refinement of each sample was carried out using different line energies of the laser beam. Estimation of the magnetic domain size was performed using the Jeffries method, the magnetic viewer was used to reveal the domain structure. The measurement of the magnetic properties was performed at a frequency of 50 Hz and an induction of 1.5 T. The analyzed results presented in this work indicate impact of laser refining on magnetic properties of grain oriented electrical steel depending on used laser beam energy.